Addiction medicine: an important field for Public Health - Martha J. Wunsch (SAGE Publishing, 2012)
The abuse of illegal drugs is one of the greatest challenges that the world is facing today. Occurring in all countries, from the richest to the poorest, it is a problem that involves all groups and, increasingly, all ages, fuelling global crime, corruption and terrorism, generating unimaginable wealth for the few and limitless harm for the many, costing millions of lives and threatening the very sustainability of communities the world over....